Нові та маловідомі види твердокрилих (Insecta, Coleoptera) у фауні Українських Карпат - Мателешко, О.Ю. (Вестник зоологии, 2009)
Впервые в Украинских Карпатах обнаружены 14 видов, из которых 10 видов и 4 рода: Liodopria serricornis (Gyllenhal, 1813); Agathidium nudum Hampe, 1871; Triarthron maerkeli W. L. E. Schmidt, 1841; Pleurotobius magnifica Roubal, 1932; Clambus pilosellus Reitter, 1876; Odontosphindus grandis Hampe, 1861; Aspidiphorus lareyniei Jacquelin du Val, 1859; Triplax elongata Lacordaire, 1842; Clemmus troglodytes Hampe, 1850; Symbiotes latus L. Redtenbacher, 1849; не были указаны ранее для Украины. Приведены новые находки трех видов: Rhopalocerus rondanii (Villa, 1833), Ditylus laevis (Fabricius, 1792), Agnathus decoratus Germar, 1818. Рассмотрены распространение и экология отдельных видов. Fourteen species are recorded for the first time in the Ukrainian Carpathians, among them 10 species and 4 genera (Liodopria serricornis (Gyllenhal, 1813), Agathidium nudum Hampe, 1871, Triarthron maerkeli W. L. E. Schmidt, 1841, Pleurotobius magnifica Roubal, 1932, Clambus pilosellus Reitter, 1876, Odontosphindus grandis Hampe, 1861, Aspidiphorus lareyniei Jacquelin du Val, 1859, Triplax elongata Lacordaire, 1842, Clemmus troglodytes Hampe, 1850, Symbiotes latus L. Redtenbacher, 1849) are new for Ukraine. The new localities of 3 species: (Rhopalocerus rondanii (Villa, 1833), Ditylus laevis (Fabricius, 1792), Agnathus decoratus Germar, 1818 are given. Distribution and ecology of some species are discussed.